ANALISIS PENGGUNAAN MEDIA BIGBOOK UNTUK KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS 1 MI ASSALAM BATU - Revina Petrika Wijayanto; Ika Ratih Sulistiani; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Reading is an activity that is very important in everyday life. Given the importance of reading skills, many parents teach reading exercises to their children from an early age. Beginning reading training in grade 1 aims to train student’s reading skills. So the researchers formulated the problem, namely 1) how the student’s initial reading skills in class 1 MI Assalam Batu and 2) how to use Bigbook media for early reading skills in class 1 MI Assalam Batu. The use of the metod in this study is a qualitative research method. This study uses data collection techniques with interviews and observations as well as documentation. Reading skills at the beginning of class 1are in the good category because there are 17 children who can read. There are several influencing factors, namely internal factors and external factors. Internal factors include students reading ability and motivational learning from parents, while external factors include the environment in which to socialize an socio-economic factors. The use of Bigbook media is very effective for grade 1 students because this media is quite interesting, it has a large size and lots of pictures and readings that are easily understood by students. With the Bigbook media, students become motivated to read and students initial reading skills increase. The obstacles faced by teachers in implementing Bigbook media are limited time and students become bored. The solution to overcome these obstacles is that the techer makes the best use of time and in dealing with students who are bored when learning the teacher invites for icebreaking on the sidelines of learning.